2012
DOI: 10.1007/s12253-012-9547-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Advanced- and Non Advanced Sporadic Polypoid Colorectal Adenomas: Correlation to KRAS Mutations

Abstract: The malignant potential of colorectal adenomas highly correlates with their pathological characteristics, such as size, histology and grade of dysplasia. Currently, based on these parameters, adenomas are characterized as "non-advanced or advanced" and patient surveillance is adjusted accordingly. The aim of this study was to investigate the correlation between the KRAS mutations and characteristics of non-advanced and advanced colorectal adenomas for predicting the risk of increased malignant potential of ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…This Our results indicated that BRAF is a prevalent marker in the serrated pathway. We observed BRAF mutation in ~40% of SAs and this is in line with previous studies that demonstrated a frequency of BRAF mutations (v600E) ranging from 32 to 82.9% (33). Collectively, our findings, as well as those of others, are in agreement with a recent study using BRAF V600E knock-in murine models that demonstrate the pivotal role of BRAF mutations in the initiation of the serrated pathway (35).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This Our results indicated that BRAF is a prevalent marker in the serrated pathway. We observed BRAF mutation in ~40% of SAs and this is in line with previous studies that demonstrated a frequency of BRAF mutations (v600E) ranging from 32 to 82.9% (33). Collectively, our findings, as well as those of others, are in agreement with a recent study using BRAF V600E knock-in murine models that demonstrate the pivotal role of BRAF mutations in the initiation of the serrated pathway (35).…”
Section: Discussionsupporting
confidence: 93%
“…KRAS mutations were significantly associated with advanced adenomas, which have a greater risk of developing into malignant tumors than non-advanced adenomas. Yadamsuren et al demonstrated that 57.5% of advanced adenomas harbored KRAS mutations compared with 31.0% of non-advanced adenomas in a series of 164 sporadic adenomas (33). These findings are in agreement with the Fearon and vogelstein model where KRAS mutation is responsible for the intermediate stage of adenoma progression (33).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, K-ras mutation does not confer to the metastatic potential of colorectal carcinomas. v. K-ras mutation does not confer to the formation of early adenomas (confirming other researchers) (32,55,82), but it rather aids the evolution of the non-advanced adenoma to the advanced one (data not shown).…”
Section: Which Established Knowledge Did Our Study Confirm?supporting
confidence: 77%
“…It is among the earliest genetic events of the process (51) although it is well known that it can occur at any stage (52). Its mutations are present in 50-95% of dysplastic ACF (34,53), in 15-78% of colorectal adenomas (54,55) and in 36-42% of CRCs (56). K-ras mutations on codons 12/13 of exon 2 and on codon 61 of exon 3 are de novo mutations whose presence depends on the random "activation" of the protooncogene K-ras during the life-span of healthy individuals either due to carcinogen exposure or to sporadic replication errors (57).…”
Section: Why Is K-ras Mutation a Potential Alternative Initiating Evementioning
confidence: 99%